TECTONOSTRATIGRAPHY OF AREA EMPAT WEST NATUNA BASIN - Trihatmojo, Adianto
Area Empat is situated at one of the sub-basins in West Natuna Basin, Kambing Graben. The area is related to at least two regional strike-slip zone, the Three Pagodas Fault Zone and Aliaoshan-Red River Fault Zone with North West-South East major structural trends. Tectonic and sedimentation history of West Natuna Barat generally developed successful hydrocarbon traps. Therefore, tectonostratigraphy analysis was carried out to further discuss the structural development of West Natuna Basin, especially of Area Empat. Six well data and 189 2D seismic data of the research area was processed. Tectonostratigraphy analysis began with interpreting 2D seismic horizons, which include horizons of pre-rift, syn-rift, post-rift and syn-inversion based on reflector unconformities. Afterwards, time structure maps and isochron maps were made for each horizon intervals. From the time structure maps, the distribution of geological structures and how they influence local deposition can be interpreted. Palinspastic reconstruction was then carried out on chosen North North West-South South East trending 2D seismic line that crossed major structures. Based on the tectonostratigraphy analysis result, pre-rift phase consists of Pre-Tertiary rocks of West Natuna Basin, syn-rift phase consists of Lama and Lower Gabus Formation, postrift phase consists of Keras and Upper Gabus Formation, then syn-inversion phase includes Arang Formation. Developed structures affected by at least two major structural trend: East South East-West North West and North East-South West.